Rethinking Negative Multiplication: Separating Magnitude from Direction - Omar Ali Zargelin (المجلة الأفروآسيوية للبحث العلمي, 2025)
Arithmetic rests on four fundamental operations, yet multiplication with negatives poses interpretational challenges that addition and subtraction do not. Historically, negative multiplication was introduced to preserve algebraic consistency and closure, but its tangible, real-world mechanism remains opaque: identities such as and are algebraically valid while lacking an intuitive model that explains how the final sign arises as a realized operation. Building on prior work that re-read division by zero and division by negatives treating some actions as nonexistent rather than merely undefined this paper re-examines the legitimacy of negative multiplication as a real operation rather than a symbolic convention. We adopt a sign–magnitude split during computation with post-hoc sign restoration and propose a two-model framework. Model I bans direction × direction: squaring a negative preserve its sign, even roots of negatives are not realized on , and negative × negative is not a realized operation. Model II allows computation with direction preservation when two negatives meet, defining even roots of negatives as the negative of the positive root on the magnitude. The framework cleanly separates outcomes that are realized on from those that are symbolic only (requiring or falling outside the domain), without altering classical algebraic truths. The result is a principled boundary between symbolic structure and physical meaning, a transparent labeling policy for instruction, and a coherent pathway to complex analysis when and only when its introduction is conceptually warranted.